Facilitators and barriers to linkage to HIV care and treatment among female sex workers in a community-based HIV prevention intervention in Tanzania: A qualitative study - Nyato, Daniel (PLoS One, 2019)
BACKGROUND: HIV-infected female sex workers (FSWs) have poor linkage to HIV care in sub-Sahara Africa. METHODS: We conducted 21 participatory group discussions (PGDs) to explore factors influencing linkage to HIV care among FSWs tested for HIV through a comprehensive community-based HIV prevention project in Tanzania. RESULTS: Influences on linkage to care were present at the system, societal and individual levels. System-level factors included unfriendly service delivery environment, including lengthy pre-enrolment sessions, concerns about confidentiality, stigmatising attitudes of health providers. Societal-level factors included myths and misconceptions about ART and stigma. On the individual level, most notable was fear of not being able to continue to have a livelihood if one’s status were to be known. Facilitators were noted, including the availability of transport to services, friendly health care providers and peer-support referral and networks. CONCLUSION: Findings of this study underscore the importance of peer-supported linkages to HIV care and the need for respectful, high-quality care.